Kurdish women's stories - Mahmoud, Houzan (University of Alberta Press, 2021)
"From all four parts of Kurdistan and across the diaspora, Kurdish women from different geographical, political, and educational backgrounds pick up a pen, reflect, and remember. Going beyond exoticising stereotypes and patriarchal representations, Kurdish Women's Stories gives 25 women authorial freedom to write about their own lived experiences. With contributors ranging from 20 to 70 years of age, we hear stories of imprisonment, exile, disappearances of loved ones, gender-based violence, uprisings, feminist activism, and armed resistance, including first-hand accounts of political moments from the 1960s to today. Conceived as part of Culture Project's self- writing program, this book is essential reading for anyone who wants to better understand the struggle of Kurdish women through their own words. Contributors: Diba Alikhani, Kobra Banehi, Khanda Hameed, Nazanin Hasan, Nafia Aysi Hasso, Deejila Haydar, Zhala Hussein, Ruken Isik, Seveen Jimo, Lanja Khawe, Nahiya Khoshkalam, Hero Kurda, Khanda Rashid Murad, Rozhgar Mustafa, Dashne Nariman, Bayan Nasih, Avan Omar, Nasrin Ramazanali, Mother Sabria, Bayan Saeed, Bayan Salman, Farah Sharefi, Susan Shahab, Simal (Anonymous), Shahla Yarhussein"--